The Bureaucracy and Financial Management of Hajj in Indonesia: An Analysis of the Legal Standing and Institutional Structure of the Badan Pengelolaan Keuangan Haji (BPKH) - Muhammad Aziz Zakiruddin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This article scrutinizes the legal standing and institutional analysis of the Hajj Financial Management Agency (BPKH) within the constitutional framework in Indonesia. Through a literature review, the author investigates and re-examines the legal standing and institutional structure of BPKH, employing a normative-empirical legal study approach that explores legal norms, regulations, or secondary legal data along with an assessment of the effectiveness of norm application. The findings and conclusions are as follows: 1) Regarding legal standing, Law Number 34 of 2014 on the Management of Hajj Finances serves as the foundation and mandate for establishing BPKH. However, a disharmony exists between Law Number 34 of 2014 on the Management of Hajj Finances and Law Number 8 of 2019 on the Implementation of Hajj Worship. 2) In terms of institutional aspects, BPKH is an independent institution as stipulated in the Law on Hajj Financial Management. Nevertheless, BPKH's independence differs from other independent institutions, leading to the conclusion that BPKH is functionally independent but not structurally independent. This research aims to serve as a reference for policymakers to strengthen and consolidate the position of BPKH